2010
DOI: 10.1111/j.1574-6941.2010.00925.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of nitrogen-fixing bacteria in cyanobacterial mats

Abstract: The structure of the microbial community and the diversity of the functional gene for dinitrogenase reductase and its transcripts were investigated by analyzing >1400 16S rRNA gene and nifH sequences from two microbial mats situated in the intertidal zone of the Dutch barrier island Schiermonnikoog. Although both microbial mat communities were dominated by Cyanobacteria, they differed with respect to the composition of the total bacterial community. Proteobacteria-related sequences were retrieved as the second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 38 publications
3
43
0
1
Order By: Relevance
“…Recently, it was shown in a New Zealand estuary that water temperature and flow can influence benthic cyanobacterium proliferation (Heath et al, 2010). The success of mat-building cyanobacteria might be due to two main factors: (i) N 2 fixation, which is another advantageous characteristic of cyanobacteria in mat environments, commonly described as nutrient-poor and nitrogen-depleted; and (ii) their ability to adapt to the wide environmental fluctuations experienced by mats (Badger et al, 2006;Severin et al, 2010). Up to now, no work on these aspects has been published for European brackish waters.…”
Section: Bloom and Mat-forming Brackish-water Cyanobacteria And Limitmentioning
confidence: 99%
“…Recently, it was shown in a New Zealand estuary that water temperature and flow can influence benthic cyanobacterium proliferation (Heath et al, 2010). The success of mat-building cyanobacteria might be due to two main factors: (i) N 2 fixation, which is another advantageous characteristic of cyanobacteria in mat environments, commonly described as nutrient-poor and nitrogen-depleted; and (ii) their ability to adapt to the wide environmental fluctuations experienced by mats (Badger et al, 2006;Severin et al, 2010). Up to now, no work on these aspects has been published for European brackish waters.…”
Section: Bloom and Mat-forming Brackish-water Cyanobacteria And Limitmentioning
confidence: 99%
“…More recently, the nifH gene has been used as a phylogenetic and functional marker for N 2 fixation and allows investigating the phylogenetic distribution of the genetic potential for N 2 fixation in complex microbial communities. Surveys of nifH in microbial mats suggested that heterotrophic bacteria might also have an important role in microbial mat N 2 fixation in addition to cyanobacteria (Zehr et al, 1995;Steppe et al, 1996;Zehr et al, 2003;Omoregie et al, 2004a;Severin et al, 2010;Severin and Stal, 2010b). Analysis and quantification of nifH transcripts have helped to identify the fraction of diazotrophs actively expressing this essential gene for N 2 fixation and has given insights into gene-expression dynamics in the environment (Omoregie et al, 2004b;Moisander et al, 2006;Severin and Stal, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Deep-sea sediments constitute the largest fraction of the Earth's surface and a vast portion of these sediments are anoxic and thus suitable habitat for microbial N 2 fixation (19); however, marine diazotrophic microbes have been studied mostly in oligotrophic surface waters (see reference 20 and references therein) and certain shallow-water benthic systems, such as salt marshes, mangroves, microbial mats and other coastal environments (21)(22)(23)(24)(25)(26). Rarely conducted investigations of the N 2 fixation microbial communities of deep-sea waters and hydrothermal vent fluids have discovered diverse and novel nifH gene sequences (12,13).…”
mentioning
confidence: 99%